Developmental Strategies of the Promotion Policies in Medical Tourism Industry in South Korea: A 10-Year Study (2009-2018) - Kyoung-Lee KIM; Byung-Ro SEO (Tehran University of Medical Sciences, 2019)
Background: After the revision of the Medical Service Act, Article 27-2, in 2009, Korea has been actively involved in the medical tourism industry. The number of foreign patients visiting Korea has consistently increased coming from various countries around the world. Currently, the industry is striving to achieve qualitative growth in medical tourism. Accordingly, there is a necessity to analyze and review policies for the development of medical tourism to create a sustainable market. Methods: We analyzed the information of foreign patients visiting Korea over a period of last 10 years. Statistical data were obtained from the Korea Health Industry Development Institute (KHIDI) and Korea Tourism Organization (KTO). Results: The number of foreign patients visiting Korea had increased from 60,201 in 2009 to 321,574 in 2017. Since 2017, the number of patients from the U.S., Russia and Middle East has been on an upward trend while the number of Chinese patients has decreased. This result clearly shows that international affairs and cultural aspects have a significant impact on the selection of medical tourism. Conclusion: It is suggested to i) establish the medical tourism information system and brand the Korean medical tourism offering a joint treatment of western and oriental medicine, ii) prepare the expansion of the industry to the medical wellness tourism industry by training global healthcare experts and iii) organize tailored medical services with consideration of various backgrounds and culture of foreign patients.